Fungsi Budaya dalam Mengoptimalkan Dialog dan Misi Kristiani - Dongoran, Lambok; Sianturi, Debora; Simanjuntak, Jusuf JR; Purba, Diva Threcia; Damanik, Dapot (Sekolah Tinggi Teologi Torsina Surakarta, 2025)
This study analyzes the function of culture in optimizing dialogue and Christian mission through an integrative approach that combines missiological anthropology, practical theology, and intercultural communication studies perspectives. The research identifies gaps in existing literature that tend to separate contextualization studies from intercultural dialogue mechanism analysis in mission contexts. Through a comprehensive analysis of cultural elements functioning as cross-cultural communication bridges, this study develops a theoretical framework for understanding how local cultural particularities can be utilized as media for conveying universal Gospel truths without compromising theological integrity. Findings indicate that cultural optimization in mission dialogue requires a deep understanding of target communities' worldviews, value systems, and social structures. This research formulates practical principles for implementing culturally informed approaches in contemporary Christian mission, contributing to developing more effective and contextually appropriate mission strategies in the globalization era characterized by increasing cultural complexity and religious pluralism. Abstrak Penelitian ini menganalisis fungsi budaya dalam mengoptimalkan dialog dan misi Kristiani melalui pendekatan integratif yang menggabungkan perspektif antropologi misiologi, teologi praktis, dan studi komunikasi antarbudaya. Studi ini mengidentifikasi kesenjangan dalam literatur eksisting yang cenderung memisahkan kajian kontekstualisasi dari analisis mekanisme dialog antarbudaya dalam konteks misi. Melalui analisis komprehensif terhadap elemen-elemen budaya yang berfungsi sebagai jembatan komunikasi lintas budaya, penelitian ini mengembangkan kerangka teoretis untuk memahami bagaimana particularitas budaya lokal dapat dimanfaatkan sebagai medium penyampaian kebenaran universal Injil tanpa mengorbankan integritas teologisnya. Temuan menunjukkan bahwa optimalisasi budaya dalam dialog misi memerlukan pemahaman mendalam tentang worldview, sistem nilai, dan struktur sosial masyarakat sasaran. Penelitian ini merumuskan prinsip-prinsip praktis untuk implementasi pendekatan yang culturally informed dalam misi Kristiani kontemporer, berkontribusi pada pengembangan strategi misi yang lebih efektif dan contextually appropriate dalam era globalisasi yang ditandai oleh increasing cultural complexity dan religious pluralism.